Comparative study of conventional and organic farming of coriander (Coriandrum sativum) -radish (Raphanus sativus) cropping sequence - Uadal Singh; Y K Sharma; R K Bagri; Ashok Choudhary; Bairwa, S K; Mahawar, A K (Current Horticulture, 2025)
An experiment was conducted to compare performance of organic and conventional management practices in coriander (Coriandrum sativum L.) and radish (Raphanus sativus L.) cropping system at Rajasthan Agricultural Research Institute, Durgapura, Jaipur, Rajasthan during 2017–18, 2018-19 and 2019–20. The conventional practices comprising integrated use of organic amendments, nutrients through chemical fertilizers and plant-protection chemicals were compared with organic management practices which comprised nutrient and pest management through organic amendments and practices. Experiment consisted of 7 treatments laid out in randomized block design. Pooled analysis revealed that, safe production practices (recommended FYM + fertilizer + plant protection with organic methods) + IIHR microbial consortium @ 12.5 kg/ha (T7) resulted in significantly higher coriander fresh green leaves yield (94.03 q/ha) and radish root yield (237.61 q/ha). It was followed by conventional practices (recommended FYM + fertilizer + plant protection with chemicals) + IIHR microbial consortium @ 12.5 kg/ha (T4) in coriander, while T6 (FYM equivalent to 100 % N recommended for each of the crop + IIHR microbial consortium @ 12.5 kg/ha (plant protection with organic methods) in case of radish. Return per rupee invested (4.00) and net return (₹.2.55 lakh/ha.) in the sequence were also maximum with treatment T7.